The Complete Works of Artemus Ward $1 (BPart 2: Wars - Ward, Artemus, 1834-1867 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Complete Works of Artemus Ward $1 (BPart 2: War" by Artemus Ward is a collection of humorous essays written during the mid-19th century, primarily during the American Civil War. The book features the wit of Artemus Ward, a comedic persona created by Charles Farrar Browne, who uses satire to address issues of war, politics, and societal norms of his time. Through the narrative, the author shares entertaining anecdotes about his experiences and observations during the war, often highlighting the absurdities of both sides of the conflict. The opening of the collection introduces the protagonist, Artemus Ward, as he recounts his travels in the South, where he encounters Southern sympathizers and local customs. He describes a comical scenario in which his wax show is confiscated by Confederate soldiers, leading to an unexpected series of misadventures and hilarity. This sets the tone for the book, revealing Ward's irreverent take on the seriousness of war, using humor to explore the stark contrasts between the varying views of patriotism in different regions. His unique voice and rich characterizations promise readers an entertaining perspective on historical events, coupled with sharp social commentary. (This is an automatically generated summary.)s
Release date is 2002-06-01
This etext was produced by anonymous Project Gutenberg Volunteers
Keywords: American wit and humor